Higher Education Reform In Thailand: Toward Quality Improvement And University Autonomy - Navy, Ammar (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2013)
Though the issue of higher education reform in Thailand has been raised for many years, it was not until the promulgation of the National Education Act in 1999 that the comprehensive reform including that of higher education really took place. In implementing the reform of higher education, Thailand has placed high importance on the reform of learning and teaching for improving students both in public and private institutions